2019
DOI: 10.1002/joom.1070
|View full text |Cite
|
Sign up to set email alerts
|

The impact of planning and communication on unplanned costs in surgical episodes of care: Implications for reducing waste in hospital operating rooms

Abstract: This ethnographic study of more than 90 surgeries (referred to as episodes of care) identifies the antecedents to operating room (OR) supply waste. The study specifically considers the role of planning instances and communication patterns among members of the surgery team on supply waste within the OR. We operationalize planning instances in terms of the number of changes to the physician preference card (PPC), the key document that is used to plan items needed for surgery. Communication patterns among members… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 99 publications
(170 reference statements)
0
14
0
Order By: Relevance
“…Some plans are updated frequently and with great detail, while other plans are rarely, if ever, updated such that different patients receive the same surgical plan. With greater planning, less waste and better outcomes are achieved (Dreyfus et al. , 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some plans are updated frequently and with great detail, while other plans are rarely, if ever, updated such that different patients receive the same surgical plan. With greater planning, less waste and better outcomes are achieved (Dreyfus et al. , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, disruptions in the healthcare industry may also manifest in other ways, such as natural disasters, supply and instrument shortages, and human error. One of the critical areas within the hospital setting prone to disruptions is the operating room (OR) department (Dreyfus et al. , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…From previous studies, it can be found that there are relatively few studies on the influencing factors of temporal team mental models, mainly focusing on the following aspects. The first is communication, which is considered the most important way of behavioral moderation in a team (Dreyfus et al, 2019). When unconscious team behavior synchronization is impossible, team members may use the explicit team communication process to make their perceptions of time reach a consensus.…”
Section: Theoretical Basis and Research Hypotheses Temporal Team Mental Model And Team Performancementioning
confidence: 99%
“…Two papers describe hospital-emergency-department operations (Berry Jaeker & Tucker, 2020;Davis, Zobel, Khansa, & Glick, 2020). Two papers (Dreyfus, Nair, & Rosales, 2020;Mukherjee & Sinha, 2020) examine perioperative services. Two papers examine operations at the level of the entire hospital (Johnson, Burgess, & Sethi, 2020;Tucker, Zheng, Gardner, & Bohn, 2020).…”
Section: Special Issue Process and Papersmentioning
confidence: 99%